Overcoming Cabbage Crossing Incompatibility by the Development and Application of Self-Compatibility-QTL- Specific Markers and Genome-Wide Background Analysis - Xiao, Zhiliang; Han, Fengqing; Hu, Yang; Xue, Yuqian; Fang, Zhiyuan; Yang, Limei; Zhang, Yangyong; Liu, Yumei; Li, Zhansheng; Wang, Yong; Zhuang, Mu; Lv, Honghao (Frontiers in Plant Science, 2019)
Cabbage hybrids, which clearly present heterosis vigor, are widely used in agricultural production. We compared two S5 haplotype (Class II) cabbage inbred-lines 87–534 and 94–182: the former is highly SC while the latter is highly SI; sequence analysis of SI-related genes including SCR, SRK, ARC1, THL1, and MLPK indicates the some SNPs in ARC1 and SRK of 87–534; semi-quantitative analysis indicated that the SI-related genes were transcribed normally from DNA to mRNA. To unravel the genetic basis of SC, we performed whole-genome mapping of the quantitative trait loci (QTLs) governing self-compatibility using an F2 population derived from 87–534 × 96–100. Eight QTLs were detected, and high contribution rates (CRs) were observed for three QTLs: qSC7.2 (54.8%), qSC9.1 (14.1%) and qSC5.1 (11.2%). 06–88 (CB201 × 96–100) yielded an excellent hybrid. However, F1 seeds cannot be produced at the anthesis stage because the parents share the same S-haplotype (S57, class I). To overcome crossing incompatibility, we performed rapid introgression of the self-compatibility trait from 87–534 to 96–100 using two self-compatibility-QTL-specific markers, BoID0709 and BoID0992, as well as 36 genome-wide markers that were evenly distributed along nine chromosomes for background analysis in recurrent back-crossing (BC). The transfer process showed that the proportion of recurrent parent genome (PRPG) in BC4F1 was greater than 94%, and the ratio of individual SC plants in BC4F1 reached 100%. The newly created line, which was designated SC96–100 and exhibited both agronomic traits that were similar to those of 96–100 and a compatibility index (CI) greater than 5.0, was successfully used in the production of the commercial hybrid 06–88. The study herein provides new insight into the genetic basis of self-compatibility in cabbage and facilitates cabbage breeding using SC lines in the male-sterile (MS) system.